FACTORS AFFECTING REPRODUCTIVE TRAITS IN SEVERAL BREEDS OF DAIRY CATTLE IN IRAQ - & Hadad, Hermiz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aimed to investigate the factors affecting reproductive traits using records collected during two calving seasons (2016-2017) and (2017-2018) from three herds of dairy cattle bred at Erbil-Iraq, and includes 323 lactation period (LP), 159 age at first calving (AFC) and 159 calving interval (CI). GLM within SAS used to diagnose the significance effects of the available factors affecting the studied traits. Repeatability of LP also estimated. Overall mean of LP, AFC and CI for the three breeds in all herds were 300.14 days, 27.709 months, and 360.26 days respectively. Simmental recorded significantly (p